Beside the berm: The convenience of roadside picking. Issue 2 (23rd April 2021) - Piacentini, Dominic
Abstract : This article gathers together stories from wild foods pickers in West Virginia's North Central Highlands who work along the side of the road. Building from anthropological scholarship in roads, roadsides, and edgework, I argue that amid neoliberal privatization, the side of the road is a convenient place to gather wild foods. Because the property along the side of the road is often confused, ignored, or mixed, it is also a convenient place to engage in forms of commoning, (re)negotiating access to wild foods and medicines, such as elderberries, sassafras, and St. John's wort. The stories presented here were collected in interviews and participant observation conducted during ethnographic fieldwork in 2019. They demonstrate the deep, more‐than‐human relationality of enviroeconomic provisioning along the side of the road.